Modern slavery and public health: a rapid evidence assessment and an emergent public health approach. (March 2020) - Such, E.; Laurent, C.; Jaipaul, R.; Salway, S.
Abstract: Objectives: Modern slavery is a human rights violation and a global public health concern. To date, criminal justice approaches have dominated attempts to address it. Modern slavery has severe consequences for people's mental and physical health, and there is a pressing need to identify and implement effective preventative measures. As such, a public health approach to modern slavery requires elucidation. The objectives of this study were to explore the case for public health involvement in addressing modern slavery and the components of a public health approach and to develop a globally relevant framework for public health action. Study design: A Rapid Evidence Assessment. Methods: This study is a rapid systematic review of published literature and stakeholder consultation. Results: The accounts of 32 consultees and evidence from 17 papers including reviews, commentaries and primary studies were included in the evidence assessment. A strong ethical rationale for public health engagement in addressing modern slavery was evident. Multilevel and multicomponent interventional strategies were identified across global, national, regional, local and service levels. Although public health could add value to existing approaches, multiple barriers and tensions exist. Conclusion: Published literature and stakeholder opinion indicate an emergent public health approach to modern slavery. It involves intervention at multiple levels and is guided by a rights-based, survivor-centred and trauma-informed approach. This synthesis offers an important early step in the construction of a globally relevant public health approach to modern slavery. Highlights: Modern slavery as a public health issue is at an early stage of development. There is a strong ethical case for public health engagement. A public health approach includes upstream prevention measures as well as victim-centred services. A holistic framework includes global-, national-, local- and service-level interventions.